Comparing memory group training and computerized cognitive training for improving memory function following stroke: A phase II randomized controlled trial - Toni D. Withiel; Dana Wong; Jennifer L. Ponsford; Dominique A. Cadilhac; Peter New; Tijana Mihaljcic; Renerus J. Stolwyk (Medical Journals Sweden, 2019)
Objectives: Memory deficits are common after stroke, yet remain a high unmet need within the community. The aim of this phase II randomized controlled trial was to determine whether group compensatory or computerized cognitive training approaches were effective in rehabilitating memory following stroke. Methods: A parallel, 3-group, single-blind, randomized controlled trial was used to compare the effectiveness of a compensatory memory skills group with restorative computerized training on functional goal attainment. Secondary outcomes explored change in neuropsychological measures of memory, subjective ratings of prospective and everyday memory failures and ratings of internal and external strategy use. Results: A total of 65 community dwelling survivors of stroke were randomized (24: memory group, 22: computerized cognitive training, and 19: wait-list control). Participants allocated to the memory group reported significantly greater attainment of memory goals and internal strategy use at 6-week follow-up relative to participants in computerized training and wait-list control conditions. However, groups did not differ significantly on any subjective or objective secondary outcomes. Conclusion: Preliminary evidence shows that memory skills groups, but not computerized training, may facilitate achievement of functional memory goals for community dwelling survivors of stroke. These findings require further replication, given the modest sample size, subjective nature of the outcomes and the absence of objective eligibility for inclusion.